Acorn flour from holm oak (Quercus rotundifolia): Assessment of nutritional, phenolic, and technological profile - Martins, Rita Beltrão (2022)
Acorn is the fruit of holm oak (Quercus rotundifolia), being mainly used nowadays to feed animals, however a substantial part remains in the fields without any valorization. Underexploited crops are gaining new interest, driven by food security concerns and health benefits potential as well. In the present work, it was studied the physicochemical characteristics and functional perspective of acorn flour, as an ingredient for human diet. The study included nutritional composition analysis, phenolic compounds profile through HPLC, starch content and its microstructure, fibre, and pasting properties assessment. Acorn flour presented a high content in fat, particularly monounsaturated and polyunsaturated (oleic and linoleic acids), and high minerals content in particular K. Concerning phenolic profile, rutin, catechin, ellagic acid, gallic acid, and syringic acid were identified. In regards to technological profile, fibre was mainly insoluble, with around 11%, and starch content was 50%. Its pasting behaviour revealed a high gelatinization temperature (85 ◦C), with low breakdown, and higher retrogradation consistency. These results show acorn flour potential as a valuable and sustainable multipurpose food ingredient